ITU PENGARUH PENDEKATAN INDIVIDU TERHADAP READING DITINJAU DARI MINAT SISWA - wiwied pratiwi (Jurnal Pedagogy, 2017)
The objectives of the research are to examine whether: (1) Individual Approach is more effective than Group Approach to teach reading at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016; (2) The students having high interest have better reading comprehension than those having low interest at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016; and (3) there is an interaction between teaching approach and students’ interest in teaching reading at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016. Based on the result of the research the writer got some research finding as follows; (1) Individual Approach is more effective than Group Approach to teach reading at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016; (2) The students having high interest have better reading comprehension than that of those having low interest at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016; and (3) There is an interaction between teaching Approach and students’ interest in learning reading comprehension at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016. Referring to the research findings, it can be concluded that individual approach is an effective approach to teach reading at the second semester of Islamic banking Study of Institut Agama Islam Ma’arif (IAIM) NU Metro in the academic year of 2015/2016. The research also shows that the implementation of two different approaches for teaching reading gives the different learning result. Finally English teachers are recommended to apply both individual approach and group approach interchangeably in teaching reading in the class.